2014
DOI: 10.1007/s12298-014-0232-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of female Ephedra foliata Boiss. & Kotschy ex Boiss.: an endemic and threatened Gymnosperm of the Thar Desert

Abstract: Ephedra foliata Boiss. & Kotschy ex Boiss., (family - Ephedraceae), is an ecologically and economically important threatened Gymnosperm of the Indian Thar Desert. A method for micropropagation of E. foliata using nodal explant of mature female plant has been developed. Maximum bud-break (90 %) of the explant was obtained on MS medium supplemented with 1.5 mg l(-1) of benzyl adenine (BA) + additives. Explant produces 5.3 ± 0.40 shoots from single node with 3.25 ± 0.29 cm length. The multiplication of shoots in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The highest percentage of shoots (73%) was rooted on NAA with less number of roots (5.8). Our result signifies that half strength of MS salts in medium is appropriate for in vitro rooting and is in line with the research work published by many authors [ 33 35 ]. Ragavendran et al [ 16 ] also rooted in vitro raised shoots by use of IBA in case of P. foetida .…”
Section: Resultssupporting
confidence: 93%
“…The highest percentage of shoots (73%) was rooted on NAA with less number of roots (5.8). Our result signifies that half strength of MS salts in medium is appropriate for in vitro rooting and is in line with the research work published by many authors [ 33 35 ]. Ragavendran et al [ 16 ] also rooted in vitro raised shoots by use of IBA in case of P. foetida .…”
Section: Resultssupporting
confidence: 93%
“…Incorporation of auxin at a lower concentration (NAA 0.1 mg l −1 ) with cytokinins in subculturing medium showed synergetic effects on shoot multiplication, as a number of shoot buds were generated at the base of shoot clump. The probable attribute for this synergism is cross-talk mechanism of auxin and cytokinins which induce new bud primordia, subsequent bud formation and shoot regeneration in cultures (Lodha et al 2014b; Zhang Once PGRs were optimized, cultures were transferred to MS modified media (MMS 1 to MMS 3 ) to study the effect of different salts concentration on further shoot multiplication. In the present study, MMS 3 medium was found better than MS medium for shoot multiplication/ growth (Fig.…”
Section: Effect Of Pgrs and Modified Media On Shoot Multiplicationmentioning
confidence: 99%
“…Rooting under ex vitro conditions is an attractive technique because it does not need any additional acclimatization prior to the field transfer (Pospóšilová et al 1999;Osório et al 2013;Lodha et al 2014b). It also requires lesser time and resources; and it is estimated that ex vitro rooting can lower the cost of a micropropagation protocol up to 70-75 % (Lodha et al 2014a;Patel et al 2014).…”
Section: Ex Vitro Rooting Of Micropropagated Shootsmentioning
confidence: 99%
“…Maximum bud (90 %) fromin vitro culture of nodal explants of E. foliata has obtained on MS medium supplemented with 1.5 mg l -1 of benzyl adenine (BA). Explant produced 5.3 shoots from single node with 3.25 cm length [48].The tissue cultures of Ephedra foliata has doneon MS medium containing 0.5 mg l−1 each of 2, 4-D and Kn. Maintained callus cultures exhibited regeneration potential and maximum number of shoots with an average height has achieved on MS medium containing combination of 0.25 mg l −1 each of Kn, BA and 0.1 mg l −1 of NAA.…”
Section: Discussionmentioning
confidence: 99%